Do Investors Value Sustainability? A Natural Experiment Examining Ranking and Fund Flows - HARTZMARK, SAMUEL M.; SUSSMAN, ABIGAIL B. (Journal of Finance, 2019)
ABSTRACT Examining a shock to the salience of the sustainability of the U.S. mutual fund market, we present causal evidence that investors marketwide value sustainability: being categorized as low sustainability resulted in net outflows of more than $12 billion while being categorized as high sustainability led to net inflows of more than $24 billion. Experimental evidence suggests that sustainability is viewed as positively predicting future performance, but we do not find evidence that high‐sustainability funds outperform low‐sustainability funds. The evidence is consistent with positive affect influencing expectations of sustainable fund performance and nonpecuniary motives influencing investment decisions.